2010
DOI: 10.3109/09638281003734441
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of post-amputation pain in upper and lower limb amputees, experience of a tertiary referral amputee clinic

Abstract: The study suggests that upper limb amputees are significantly more likely to suffer post-amputation pain which is more frequent, longer lasting and more severe in intensity when compared to lower limb amputees. This is accompanied by reduced HR-QOL especially that related to bodily pain, social function and mental health. The overall health status of amputees are also significantly lower compared to the Australian population norm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Differences between group scores were approximately 5 points, which are within the established MID of 4–6 points. 32 Previous studies have found greater experiences of pain in people with LLL compared to people without LLL, 1,2,34,35 and one study found that more than 90% of 255 participants with LLL reported chronic experiences with pain. 11 Additionally, participants with dysvascular etiology had significantly greater pain interference than people with traumatic etiology.…”
Section: Discussionmentioning
confidence: 98%
“…Differences between group scores were approximately 5 points, which are within the established MID of 4–6 points. 32 Previous studies have found greater experiences of pain in people with LLL compared to people without LLL, 1,2,34,35 and one study found that more than 90% of 255 participants with LLL reported chronic experiences with pain. 11 Additionally, participants with dysvascular etiology had significantly greater pain interference than people with traumatic etiology.…”
Section: Discussionmentioning
confidence: 98%
“…This is despite upper extremity amputations having a greater impact on a patient's quality of life than lower extremity amputations. 9,10 In addition, upper extremity amputations make up between 18% and 50% [11][12][13] of all amputations sustained in combat but only about 6% of all combat-related late amputations. 14 There have been numerous studies published examining both acute and late major amputations caused by extremity trauma during the Operation Iraqi Freedom, Operation Enduring Freedom, and Operation New Dawn conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of etiology, a leg amputation is usually followed by major physical and psychosocial challenges that severely influence the person concerned (Murray & Forshaw, 2013;Norlyk, Martinsen, & Kjaer-Petersen, 2013;Ostler, Ellis-Hill, & Donovan-Hall, 2014;Washington & Williams, 2016). Reduced quality of life (Davidson, Khor, & Jones, 2010;Remes et al, 2010), significantly higher levels of social isolation, depression, and post-traumatic disorder (Horgan & MacLachlan, 2004;Remes et al, 2010) are reported particularly in the first year after the amputation (Phelps, Williams, Raichle, Turner, & Ehde, 2008). Furthermore, a leg amputation includes an existential dimension that refers to limitation of action space and loss of freedom experienced as an exclusion from life (Norlyk et al, 2013).…”
Section: Articlementioning
confidence: 99%